2015
DOI: 10.1515/bejm-2014-0077
|View full text |Cite
|
Sign up to set email alerts
|

Household saving in Australia

Abstract: This paper investigates household saving behavior in Australia, as well as the drivers behind the recent rise in the aggregate household saving ratio. Our results explaining differences in saving behavior across households are consistent with theory and previous findings. As might be expected, households’ saving ratios tend to increase with income, but decrease with wealth and gearing. More at-risk households such as single-parent and migrant households tend to save more than other households, all else being e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Second, household saving ratios sharply increased around the GFC (see Finlay and Price, 2014). The increase in the household saving ratio since the GFC mirrors that observed in other advanced countries, although the extent of the increase in Australia is relatively large (Figure 7).…”
supporting
confidence: 53%
“…Second, household saving ratios sharply increased around the GFC (see Finlay and Price, 2014). The increase in the household saving ratio since the GFC mirrors that observed in other advanced countries, although the extent of the increase in Australia is relatively large (Figure 7).…”
supporting
confidence: 53%
“…Braun et al (2009), Curtis et al (2017), andLugauer et al (2019) all found a negative relationship between the number of dependent children in the family and the household saving rate. Finlay and Price (2015) provided further empirical evidence that single-parent households tend to save more than other households.…”
Section: Literature Reviewmentioning
confidence: 92%
“…For instance, Harris (2002) found that the current income is the most important factor determining household savings in Australia. Finlay and Price (2015) found that households, whose current income level is above their permanent income level, tend to save more. Bonham and Wiemer (2013) concluded that the rapid increase in China's national saving rate in the 2000s is largely explained by high rates of GDP growth.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with theory and previous findings, households' saving ratios in Australia also tend to increase with income, but decrease with wealth and gearing. More at-risk households such as single-parent and migrant households tend to save more than other households, all else being equal (Finlay and Price, 2015).…”
mentioning
confidence: 99%